Gender Paradigm in Fiqh: A Critical Analysis of Traditional Islamic Legal Understanding - Fithriani, Ahda; Faridah, Faridah (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract The gender paradigm in Islamic law has been a subject of critical analysis, particularly regarding traditional interpretations that establish hierarchical gender roles. While some classical understandings are influenced by patriarchal norms, contemporary thinkers propose reinterpretations using feminist hermeneutics to highlight aspects of justice and equality in religious texts. This study evaluates traditional Islamic legal understandings related to gender issues, aiming to reassess interpretations that may no longer be relevant to the current social context. The evaluation addresses gender inequality and discrimination resulting from biased legal interpretations and responds to changing social and political dynamics in contemporary Muslim societies. It promotes a more inclusive understanding of women's roles in Islam, considering religious texts and the social and cultural contexts in which the law is applied. The study's relevance lies in its efforts to harmonize Islamic law with principles of gender justice, providing a space for constructive dialogue between Islamic tradition and evolving global norms. It responds to the growing awareness and demands of Muslim women worldwide for equal rights within the context of Islamic law. By critiquing and reconstructing laws deemed biased, this study contributes to creating a more inclusive and equitable legal framework that respects women's rights without compromising the fundamental principles of Sharia. Keywords: Gender Paradigm, Feminist Hermeneutics, Gender Justice, Islamic Legal Interpretation Abstrak Paradigma gender dalam hukum Islam telah menjadi subjek analisis kritis, terutama terkait dengan interpretasi tradisional yang menetapkan peran gender yang hierarkis. Meskipun beberapa pemahaman klasik dipengaruhi oleh norma-norma patriarkal, pemikir kontemporer mengusulkan reinterpretasi menggunakan hermeneutika feminis untuk menyoroti aspek keadilan dan kesetaraan dalam teks-teks agama. Studi ini mengevaluasi pemahaman hukum Islam tradisional terkait isu-isu gender, dengan tujuan menilai kembali interpretasi yang mungkin tidak lagi relevan dengan konteks sosial saat ini. Evaluasi ini menangani ketidaksetaraan dan diskriminasi gender yang diakibatkan oleh interpretasi hukum yang bias, serta merespons dinamika sosial dan politik yang berubah di masyarakat Muslim kontemporer. Studi ini mendorong pemahaman yang lebih inklusif tentang peran perempuan dalam Islam, dengan mempertimbangkan teks-teks agama serta konteks sosial dan budaya di mana hukum diterapkan. Relevansi studi ini terletak pada upayanya untuk menyelaraskan hukum Islam dengan prinsip-prinsip keadilan gender, serta menyediakan ruang untuk dialog konstruktif antara tradisi Islam dan norma-norma global yang berkembang. Studi ini merespons meningkatnya kesadaran dan tuntutan perempuan Muslim di seluruh dunia untuk mendapatkan hak yang setara dalam konteks hukum Islam. Dengan mengkritik dan merekonstruksi hukum yang dianggap bias, studi ini berkontribusi pada penciptaan kerangka hukum yang lebih inklusif dan adil yang menghormati hak-hak perempuan tanpa mengorbankan prinsip-prinsip dasar syariah. Kata Kunci: Paradigma Gender, Hermeneutika Feminis, Keadilan Gender, Interpretasi Hukum Islam